The New Oral Anticoagulants for the Treatment of Venous Thromboembolism: A New Paradigm Shift in Antithrombotic Therapy - Taki Galanis, MD; Gina Keiffer, MD; Geno Merli, MD (Elsevier, 2014)
Background: Several novel oral anticoagulants have been studied for the prevention and treatment of venous thromboembolism (VTE) in different patient populations. Clinicians will increasingly encounter scenarios in which they must choose among these and conventional anticoagulants for the treatment of this potentially fatal condition. Objective: To review the results of Phase III clinical trials that investigated the novel oral anticoagulants for the treatment of deep vein thrombosis and pulmonary embolism. Potential advantages and disadvantages of these anticoagulant agents with respect to each other and conventional therapy will also be explored through a case-based approach. Methods: A literature search in PubMed was conducted that identified Phase III clinical trials investigating the novel oral anticoagulant agents for the treatment of VTE. Results: The new oral anticoagulant agents have been shown to be as safe and effective for the treatment of VTE as conventional therapies. Conclusions: These novel, oral anticoagulant agents are legitimate options for the treatment of VTE. A careful assessment of a patient׳s comorbidities, medication use, and laboratory results should be undertaken before prescribing the new oral anticoagulant agents for patients with VTE.